2019
DOI: 10.1021/acs.langmuir.9b02259
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-Based Sorbent for CO2 Capture: Preparation and Performance Evaluation

Abstract: In this work, zeolite-based sorbents were developed from gasified rice husk. CO2 capture capacity of the sorbents was examined at various temperatures and pressures employing a fixed-bed flow reactor and simulated flue gas. Various physicochemical properties such as thermal stability, pore size distribution, morphology, chemical composition, etc. of the in-house-developed materials were characterized in detail and were also compared with two commercially available zeolites. Tetra-ethylenepentamine was impregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…As described above, Y-type zeolites hold a well-dened pore structure and their pore sizes are of the same magnitude as CO 2 molecules, thus projected to give a great affinity for CO 2 adsorption. Murge et al 100 used zeolite-Y (designated as Z-Y-3, silica to alumina ratio of 2.25) with TEPA modication displayed higher CO 2 uptake, and the acquired results were about 114 mg g À1 and 190 mg g À1 for 1 bar and 5 bar pressure, accordingly at 303 K. Wang et al 101 used PEI impregnated mesoporous ZSM-5 zeolite prepared from rice husk ash. The measurement of the CO 2 capture at 393 K revealed that ZSM-5-PEI-30 had a capacity of 1.96 mmol g À1 , which was nearly 5 times more than the pristine.…”
Section: Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, Y-type zeolites hold a well-dened pore structure and their pore sizes are of the same magnitude as CO 2 molecules, thus projected to give a great affinity for CO 2 adsorption. Murge et al 100 used zeolite-Y (designated as Z-Y-3, silica to alumina ratio of 2.25) with TEPA modication displayed higher CO 2 uptake, and the acquired results were about 114 mg g À1 and 190 mg g À1 for 1 bar and 5 bar pressure, accordingly at 303 K. Wang et al 101 used PEI impregnated mesoporous ZSM-5 zeolite prepared from rice husk ash. The measurement of the CO 2 capture at 393 K revealed that ZSM-5-PEI-30 had a capacity of 1.96 mmol g À1 , which was nearly 5 times more than the pristine.…”
Section: Zeolitesmentioning
confidence: 99%
“…As described above, Y-type zeolites hold a well-defined pore structure and their pore sizes are of the same magnitude as CO 2 molecules, thus projected to give a great affinity for CO 2 adsorption. Murge et al 100 used zeolite-Y (designated as Z-Y-3, silica to alumina ratio of 2.25) with TEPA modification displayed higher CO 2 uptake, and the acquired results were about 114 mg g −1 and 190 mg g −1 for 1 bar and 5 bar pressure, accordingly at 303 K.…”
Section: Porous Materialsmentioning
confidence: 99%
“…With decreased Si/Al ratio, the adsorption affinity for CO 2 increases due to strong ion‐quadruple interactions [96] . In addition, FAU zeolites feature a high aluminum content, which, in principle, could enhance the CO 2 absorption capacity and selectivity [97,98] …”
Section: Zeolitesmentioning
confidence: 99%
“… 1 , 2 Capturing CO 2 from industrial emissions is one of the several approaches toward this end. 3 Solid sorbents such as zeolites, 4 metal–organic frameworks (MOFs), 5 , 6 covalent organic frameworks (COFs), 7 mesoporous carbon, 8 and metal oxides 9 have all shown to be promising materials for CO 2 capture. Among the solid CO 2 sorbents, layered double hydroxide (LDH)-derived mixed metal oxides (MMOs) have shown promising CO 2 capture performance at the 200–500 °C temperature range that is associated with industrial emissions such as iron and steel plants.…”
Section: Introductionmentioning
confidence: 99%